2012
DOI: 10.1093/nar/gks774
|View full text |Cite
|
Sign up to set email alerts
|

p32/gC1qR is indispensable for fetal development and mitochondrial translation: importance of its RNA-binding ability

Abstract: p32 is an evolutionarily conserved and ubiquitously expressed multifunctional protein. Although p32 exists at diverse intra and extracellular sites, it is predominantly localized to the mitochondrial matrix near the nucleoid associated with mitochondrial transcription factor A. Nonetheless, its function in the matrix is poorly understood. Here, we determined p32 function via generation of p32-knockout mice. p32-deficient mice exhibited mid-gestation lethality associated with a severe developmental defect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
204
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(221 citation statements)
references
References 55 publications
17
204
0
Order By: Relevance
“…Phosphorylation of p32/gC1qR by the viral kinase pUL97 was demonstrated previously (33). In the present work, p32/gC1qR localization changed from a tubular cytoplasmic localization (mitochondria-associated in mock-infected cells) (36) to a punctate, granular-shaped cytoplasmic localization with some faint staining in the nucleus of infected cells (Fig. 4, panels l-p).…”
Section: Identification Of Postulated Components Of the Hcmv-specificsupporting
confidence: 82%
“…Phosphorylation of p32/gC1qR by the viral kinase pUL97 was demonstrated previously (33). In the present work, p32/gC1qR localization changed from a tubular cytoplasmic localization (mitochondria-associated in mock-infected cells) (36) to a punctate, granular-shaped cytoplasmic localization with some faint staining in the nucleus of infected cells (Fig. 4, panels l-p).…”
Section: Identification Of Postulated Components Of the Hcmv-specificsupporting
confidence: 82%
“…The interaction of UL47 with p32 was confirmed in HSV-1-infected cells: p32 coprecipitated with MEF-tagged UL47 in lysates of cells infected with recombinant virus YK536 (MEF-UL47). p32 is a ubiquitous protein in most cell types and a multifunctional protein regulating various cellular functions, including apoptosis, RNA splicing, mitochondrial translation and metabolism, and autophagy (27,(59)(60)(61)(62). We also found that p32 accumulated at the nuclear rim in HSV-1-infected cells and that UL47 was required for the p32 accumulation.…”
Section: Discussionmentioning
confidence: 63%
“…human immunodeficiency virus type 1 Rev (44) and Tat (43), hepatitis C virus core protein (46), EBNA-1 of Epstein-Barr virus (54), and open reading frame P of HSV (55). The intracellular localization and function of p32 have been demonstrated primarily as a mitochondrial membrane protein in harakiri-mediated apoptosis (42), a mitochondrial antiviral signaling protein-interacting protein in RNAinduced retinoic acid-inducible gene I signaling (35), an interactor of splicing factor SF2/alternative splicing factor for RNA splicing (41), and an RNA-interacting protein for the translation of mitochondrial RNA (56). To date, the only viral kinase reported to associate with intracellular p32 is human CMV pUL97, a kinase that phosphorylates nuclear lamina at the inner nuclear membrane (45).…”
Section: Discussionmentioning
confidence: 99%